Identifying fundamental goals of childbirth care for women with higher body weight in Swiss maternity care: an embedded mixed methods multi-stakeholder study - Jennifer Inauen; Carmen Wyss; Judit Lienert; Evelyne M Aubry (BMJ Open)
Objectives The first objective of the study was to identify fundamental goals of childbirth care for women with higher body weight to inform decision-making processes by drawing on multi-stakeholder insights. The second objective included evaluating the method used to support these stakeholders in generating a more diverse set of fundamental goals.Design Using an embedded mixed methods design, we engaged key stakeholders in two group workshops and 11 individual interviews to identify goals considered fundamentally important for achieving the best possible childbirth care. Participants individually brainstormed childbirth care goals, selected additional goals from a pre-established masterlist and discussed them. Thereafter, participants rated the goals’ perceived importance for decision-making on a Likert scale. We thematically analyzed the goals and mapped them onto a means-ends network to identify and refine a set of fundamental goals. Methodological evaluations involved descriptive statistics and non-parametric testing.Setting Swiss maternity care.Participants 21 stakeholders, including seven women with a preconceptional body mass index ≥ 30 kg/m2, nine midwives, and five obstetricians experienced in maternity care for women with higher body weight.Results We identified eight fundamental goals of childbirth care: low maternal and neonatal complication rates, physiological childbirth processes, positive initiation of bonding and breastfeeding, positive psychosocial care experience, low physical strain for care providers, low resource use in care setting, and low direct costs of childbirth care. Individual participants generated more diverse fundamental goals on average by combining individual brainstorming with goal selection from a masterlist than by brainstorming alone. A theoretical maximum of six participants captured all eight fundamental goals.Conclusions The fundamental goals provide a framework for benchmarking decisions to improve childbirth care for women with higher body weight. Additionally, individual brainstorming combined with goal selection from a masterlist appears to be a useful method for generating a diverse set of fundamental goals in a healthcare context, even with relatively few participants.